1997
DOI: 10.1126/science.275.5302.964
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Putative Progenitor Endothelial Cells for Angiogenesis

Abstract: Putative endothelial cell (EC) progenitors or angioblasts were isolated from human peripheral blood by magnetic bead selection on the basis of cell surface antigen expression. In vitro, these cells differentiated into ECs. In animal models of ischemia, heterologous, homologous, and autologous EC progenitors incorporated into sites of active angiogenesis. These findings suggest that EC progenitors may be useful for augmenting collateral vessel growth to ischemic tissues (therapeutic angiogenesis) and for delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

125
6,623
7
164

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8,078 publications
(6,919 citation statements)
references
References 30 publications
125
6,623
7
164
Order By: Relevance
“…They concluded that CEC expression is related to both vascular disease and risk factors for vascular disease. CECs can be derived from the vascular wall (mature CECs), or EPCs (Asahara et al., 1997). Our results showed that CEC counts had no significant correlation with EPC counts ( p  > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that CEC expression is related to both vascular disease and risk factors for vascular disease. CECs can be derived from the vascular wall (mature CECs), or EPCs (Asahara et al., 1997). Our results showed that CEC counts had no significant correlation with EPC counts ( p  > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…(1997). Following hypoxia or vascular injury, EPCs are recruited into the systemic circulation by secretion of various proangiogenic cytokines (Heil, Ziegelhoeffer, Mees, & Schaper, 2004; Khakoo & Finkel, 2005; Takahashi et al., 1999; Timmermans et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…EPCs were isolated primarily in 1997 by Asahara et al [1], and since then has been extensively studied not only in biologic characteristics but functional implication. EPCs have been shown to express the endothelial cell surface antigens CD34, KDR and stem cell surface antigens CD133, and uptake AcLDL, so we can isolate or identify by these markers [11-15].…”
Section: Discussionmentioning
confidence: 99%
“…Since endothelial progenitor cells (EPCs) from peripheral blood (PB) were initially discovered and identified using the magnetic cells sorting method in 1997 by Asahara and his group [1], several researchers have found that EPCs existed in bone marrow, cord blood, and embryo-tissues, and that minimal number of EPCs also existed in heart, big blood vessel, skeletal muscle and fat tissue. So far, phenotypes of EPCs have remained to be determined, and exact differentiation has been still an ongoing debate topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation